Influence of tobacco Flower bud extract on microbial community and aroma quality during cigar leaves fermentation - Yao, Lan; Shan, Yule; Chen, Guangyu; Wang, Jiao; Yang, Jingpeng; Yu, Jun; Yang, Chunlei; Chen, Xiong (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionTobacco flower buds play a crucial role in enhancing the aroma quality of cigar tobacco leaves (CTLs). By incorporating tobacco flower bud extract into the fermentation process, this study investigates its effects on microbial community dynamics and the volatile aroma compounds in CTLs, aiming to improve cigar flavor and quality during fermentation.MethodsTo investigate the effects of tobacco flower bud extract on microbial communities and aroma quality during the fermentation of cigar tobacco leaves, volatile aroma components were evaluated using gas chromatography-mass spectrometry (GC-MS). The microbial community dynamics across different fermentation stages were analyzed using metagenomic sequencing.Results and DiscussionResults revealed that tobacco flower buds contain 23 characteristic aroma compounds, including β-ionone and phenylethanal. Notably, the extract induced a pronounced microbial shift, enriching Aspergillus in unfermented leaves and promoting Staphylococcus dominance (97%–98%) during fermentation. This shift facilitated carbohydrate and protein degradation, significantly reducing nicotine content (P < 0.001), increased total sugar (12.5%–18.75%) and reducing sugar levels (13.04%–27.27%), and optimized the potassium-to-chloride ratio. Aroma analysis demonstrated significant enrichment of carotenoid degradation products (farnesyl acetone, citronellal) and Maillard reaction products (5-methyl-2-furaldehyde) in the FE group, with total aroma content increasing by 11.9% compared to control (FW). Metagenomic functional analysis further indicated that the extract inhibited pathways related to harmful metabolite synthesis (47.0% reduction) and enhanced carbohydrate metabolism (30.6% increasing). This study confirms that tobacco flower bud extract reshapes microbial communities and metabolic networks by simultaneously suppressing harmful microbes and enhancing aroma, providing theoretical support for optimizing cigar fermentation and agricultural waste utilization.